Linear momentum and impulse experimentation tool using infrared and load cell sensors based on Internet of Things - Zahrotiy Irsyad; Yulkifli; Asrizal; Yenni Darvina (RESSTECH, 2024)
Microcontrollers can be utilized in the field of physics education as a component to develop physics experimental tools. This research aims to design and build an experimental tool that can be used to measure linear momentum and impulse with high accuracy, using Internet of Things technology. This tool utilizes infrared sensors and load cells as the main components in the measurement. The infrared sensor is used to detect the speed of the object, while the load cell is used to measure the mass of the object. The data obtained from these two sensors is sent in real-time through the IoT platform. This tool is designed to make it easier for users, especially in the educational environment, to conduct physics experiments related to momentum and impulse more efficiently and effectively. From the research that has been done, the results of performance specifications on the experimental tool and design specifications on the experimental tool are obtained. The results of performance specifications, the sensors used have good linearity with R-Square values of 0.99849, electronic circuits using various components, and blynk interfaces to display data. The results of the design specifications have an accuracy rate of 96,781% and a high measurement accuracy of 99.002% and 93.567%.